From hair to liver: emerging application of hair follicle mesenchymal stem cell transplantation reverses liver cirrhosis by blocking the TGF-β/Smad signaling pathway to inhibit pathological HSC activation - Qi Liu; Chengqian Lv; Yanan Jiang; Kunpeng Luo; Yang Gao; Jingyang Liu; Xu Zhang; Jan Mohammad Omar; Shizhu Jin (PeerJ, 2022)
Liver cirrhosis (LC) involves multiple systems throughout the body, and patients with LC often die of multiple organ failure. However, few drugs are useful to treat LC. Hair follicle mesenchymal stem cells (HF-MSCs) are derived from the dermal papilla and the bulge area of hair follicles and are pluripotent stem cells in the mesoderm with broad prospects in regenerative medicine. As an emerging seed cell type widely used in skin wound healing and plastic surgery, HF-MSCs show considerable prospects in the treatment of LC due to their proliferation and multidirectional differentiation capabilities. We established an LC model in C57BL/6J mice by administering carbon tetrachloride (CCl4) and injected HF-MSCs through the tail vein to explore the therapeutic effects and potential mechanisms of HF-MSCs on LC. Here, we found that HF-MSCs improved liver function and ameliorated the liver pathology of LC. Notably, PKH67-labeled HF-MSCs were detected in the injured liver and expressed the hepatocyte-specific markers cytokeratin 18 (CK18) and albumin (ALB). In addition, in contrast to that in the LC group, the α-SMA expression showed a decreasing trend in the treatment group in vitro and in vivo, indicating that the pathological activation of hepatic stellate cells (HSCs) was inhibited by HF-MSC treatment. Moreover, the levels of transforming growth factor β (TGF-β1) and p-Smad3, a signaling molecule downstream of TGF-β1, were increased in mice with LC, while HF-MSC treatment reversed these changes in vivo and in vitro. Based on these findings, HF-MSCs may reverse LC by blocking the TGF-β/Smad pathway and inhibiting the pathological activation of HSCs, which may provide evidence for the application of HF-MSCs to treat LC.